On the use of low terahertz band for 5G indoor mobile networks. (November 2015) - Yilmaz, Turker; Akan, Ozgur B.
Abstract: Mobile data traffic is constantly rising at huge growth rates. One evolving method to counter this expansion is operation frequency, and so bandwidth, increase, as formal standardization activities on 60 gigahertz industrial, scientific and medical radio band began in 2005. In line with this, this paper proposes the utilization of low terahertz (THz) band for the next-generation of mobile and wireless communications systems. Following the introduction and an overview of the low-THz band propagation properties, representative indoor simulations comparing the current fourth generation and proposed high frequency fifth generation networks are presented. The results show that, while it is possible to form and maintain stable communication links at low-THz band, techniques to reduce signal attenuation should be researched within all related subjects.